One Platform, a Thousand Worlds: On Twitter Irony in the Early Response to the COVID-19 Pandemic in Italy. (July 2020) - Vicari, Stefania; Murru, Maria Francesca
On 22 February 2020, 11 municipalities in Northern Italy became the first COVID-19 red zone of Europe. Two days later, when it became evident that the virus had been spreading in the country for weeks, Italy entered a "buffer zone, " a temporal zone between normality and pandemic. The buffer zone lasted around 2 weeks and thrived with irony flowing on social media through memes, multimedia remixes, and jokes. As a collective ritual, irony allowed people to temporarily background the mounting feelings of bewilderment and uncertainty by foregrounding the familiar scripts of playful and grassroots expressivity typical of networked publics. While giving the country a way to breathe before grieving, irony delivered both traditional political satire and new symbolic arrangements to frame "us" versus "them": Northern Italy versus Southern Italy, Italy versus China. We advance initial reflections on irony and its functions during what we call Italy's COVID-19 buffer zone and argue for the need of more platform research interested in how users appropriate devices and vernaculars in ways that are culturally bound. In other words, can we rethink "The Platform" (e.g., Twitter, Facebook, Instagram) as a constellation of small-world-platforms—sometimes overlapping, other times segregating—each shaped by local hopes and fears, histories and events?